METAPHORICAL SPACES IN MARDI LUHUNG’S POETRY: A HERMENEUTIC AND SEMIOTIC APPROACH TO INDONESIAN LITERARY IDENTITY - Dian Arsitades Wiranegara; Muchamad Adam Basori; Prima Purbasari (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2026)
Metaphors are essential in shaping meaning in poetry, particularly regarding identity, culture, and philosophy. This study analyzes metaphorical expressions in Mardi Luhung’s poetry through Michael Halley’s metaphorical space theory and semiotic-hermeneutic analysis. It reveals that Luhung employs human, nature-based, and mythological metaphors, each with distinct functions: human metaphors reflect identity struggles, natural metaphors highlight environmental consciousness, and mythological metaphors offer insights into cultural heritage. The research underscores the integration of ethos, logos, and pathos in his work and contributes to understanding contemporary Indonesian poetry's socio-political and philosophical dimensions, suggesting future cross-cultural comparisons in Southeast Asian poetry.